A Web-Based Nutrition Program Reduces Health Care Costs in Employees With Cardiac Risk Factors: Before and After Cost Analysis - Sacks, Naomi; Cabral, Howard; Kazis, Lewis E; Jarrett, Kelli M; Vetter, Delia; Richmond, Russell; Moore, Thomas J (Journal of Medical Internet Research, 2009)
Background Rising health insurance premiums represent a rapidly increasing burden on employer-sponsors of health insurance and their employees. Some employers have become proactive in managing health care costs by providing tools to encourage employees to directly manage their health and prevent disease. One example of such a tool is DASH for Health, an Internet-based nutrition and exercise behavior modification program. This program was offered as a free, opt-in benefit to US-based employees of the EMC Corporation. Objective The aim was to determine whether an employer-sponsored, Internet-based diet and exercise program has an effect on health care costs. Methods There were 15,237 total employees and spouses who were included in our analyses, of whom 1967 enrolled in the DASH for Health program (DASH participants). Using a retrospective, quasi-experimental design, study year health care costs among DASH participants and non-participants were compared, controlling for baseline year costs, risk, and demographic variables. The relationship between how often a subject visited the DASH website and health care costs also was examined. These relationships were examined among all study subjects and among a subgroup of 735 subjects with cardiovascular conditions (diabetes, hypertension, hyperlipidemia). Multiple linear regression analysis examined the relationship of program use to health care costs, comparing study year costs among DASH participants and non-participants and then examining the effects of increased website use on health care costs. Analyses were repeated among the cardiovascular condition subgroups. Results Overall, program use was not associated with changes in health care costs. However, among the cardiovascular risk study subjects, health care costs were US$827 lower, on average, during the study year (P= .05; t729 = 1.95). Among 1028 program users, increased website use was significantly associated with lower health care costs among those who visited the website at least nine times during the study year (US$14 decrease per visit; P = .04; t1022 = 2.05), with annual savings highest among 80 program users with targeted conditions (US$55 decrease per visit; P < .001; t74 = 2.71). Conclusions An employer-sponsored, Internet-based diet and exercise program shows promise as a low-cost benefit that contributes to lower health care costs among persons at higher risk for above-average health care costs and utilization.